Expressive Illocution Speech in The Novel "Al-Lissu Wa Al-Kilāb" By Naguib Mahfouz (Pragmatic Study) - Amir, Abd Razak; Masyitoh, Siti; Amiq, Amiq (Lughaat: Journal of Arabic Linguistics, 2025)
The novel Al-Lissu wa Al-Kilaab is one of the novels by Naguib Mahfouz containing the story of a prisoner who wants to take revenge on his best friend. The main character in this novel is Said Mahran who works as a thief with his wife and best friends, Ilish and Nabawiyya. This novel tells the theft carried out by them, namely Rauf and Said. Both are teachers and students who collaborated in the theft. However, in the middle of carrying out the action, Rauf suddenly called the police and informed him of the theft committed by Said. Said was arrested and imprisoned, not to mention his wife and co-workers who wanted to help him because they had worked together to arrest him. The conflict begins when Said comes out of prison and wants to take revenge on those who have betrayed him. Because of the feeling of anger and annoyance that rages in the chest, it shows the attitude of speech actions born from a person's psychological state. In this case, speech acts born due to psychological conditions were found in pragmatic studies, namely expressive illocution speech. The approach is more suitable for understanding the concept of expressive speech in the novel. Thus, this research discusses the form and function of expressive speech in the novel Al-Lissu wa Al-Kilaab.The objectives of this research are: first, to describe the form of expressive speech in the novel Al-lissu wa Al-Kilaab by Naguib Mahfouz. Second, describing the expressive function in the novel Al-Lissu wa Al-Kilaab by Nanguib Mahfouz. The research method used in this study is the descriptive analytical method. The data collection method carried out is by the Determinant Element Sorting Technique (PUP). The analysis method used in this study is the extra-lingual matching method. The result of this research is to describe the form and expressive function contained in the novel Al-Lissu wa Al-Kilaab by Naguib Mahfouz. In this study, three types of speech acts were found, namely literal direct speech, literal indirect speech, and non-literal indirect speech. The function of expressive speech in the novel Al-Lissu wa Al-Kilaab shows feelings of anger, confidence, sadness, hope, gratitude, complaining, and farewell.